Developing emotional intelligence in student nurse leaders: a mixed methodology study - Heather M Szeles (Elsevier, 2015)
Objective: The purpose of this mixed method, exploratory study was to measure the impact of a peer coaching program on the measured emotional intelligence (EI) of a group of student nurse leaders. Methods Participation in the study was offered to nurses in the Student Ambassador program. Students who consented received instruction on EI and its importance in leadership. Participants then took a preintervention EI test (The Mayer-Salovey-Caruso EI Test, version 2 [MSCEIT]) to obtain a baseline EI ability score. Students then participated in a series of peer coaching sessions across a semester. Participants then completed a postintervention MSCEIT test, and also a qualitative survey. Results: The analysis of the paired sample t-test showed that there was not a statistically significant difference in the total group EI scores from pre to posttest, t (8) = 0.036 >0.05; however, 80% of participants reported perceived changes in EI ability due to the intervention and 90% reported that peer coaching was beneficial to their leadership development. Conclusions: This study contributes to the body of EI literature and research on nursing education and leadership development.